2020
DOI: 10.1038/s41598-020-66731-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymer photonic crystal membrane for thermo-regulating textile

Abstract: We study numerically the absorption and scattering properties of a polymer photonic membrane to thermoregulate the human body microclimate which corresponds to the area between the skin and a textile. We first show that the structuration of the absorbing photonic membrane with air holes leads to a modulation of the optical spectrum in the Mid-infrared range. indeed, we show that the membrane is able to modulate the transmission amplitude by 28% in benefit or deficit of both the absorption and reflection. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A polymer photonic membrane with air holes can modulate the optical spectrum in the MIR range and thermoregulate the human body microclimate. Photonic crystal structure as a heating membrane helps towards reducing the room set-point temperature by 1 C. 73 Fabric coated by nano-gradient MoOx absorber not only reflects the body thermal radiation but also absorbs sunlight and converts it into heat, and successfully reaches a surface temperature up to 90 C under one sun illumination. 74 Carbon-based materials have been also used for the fabrication of radiative heating membranes.…”
Section: Radiative Heating Membranesmentioning
confidence: 99%
“…A polymer photonic membrane with air holes can modulate the optical spectrum in the MIR range and thermoregulate the human body microclimate. Photonic crystal structure as a heating membrane helps towards reducing the room set-point temperature by 1 C. 73 Fabric coated by nano-gradient MoOx absorber not only reflects the body thermal radiation but also absorbs sunlight and converts it into heat, and successfully reaches a surface temperature up to 90 C under one sun illumination. 74 Carbon-based materials have been also used for the fabrication of radiative heating membranes.…”
Section: Radiative Heating Membranesmentioning
confidence: 99%
“…where Qgen (the metabolic heat generation per unit area) is assumed to be 73 W/m 2 corresponding to the human body in a sedentary state 26,27 , Qrad,s represents the heat flux radiated from the skin, Qrad,e is the heat flux radiated from the atmosphere to the human body, Qrad,i is the heat flux radiated from the inner surface of the textile, Qrad,o is the heat flux from the outer surface of the textile to the external environment, Qcond,a represents the conduction heat flux between the skin and the clothings, Qconv is the heat convection between the clothing and the external environment. ρ i and ρ o are the IR reflectance of the inner and outer textile, respectively.…”
Section: Heat Transfer Pathways In Body Microclimatementioning
confidence: 99%
“…In addition, thermal conduction ( Qcond, f ) is the primary heat transfer mechanism of textile. Taking into account the temperature profile of textile, the inner and outer surface temperatures of the textile can be analyzed as follows 26,27,29 :…”
Section: Heat Transfer Pathways In Body Microclimatementioning
confidence: 99%
“…The embedding of nanopores into PE microfibers not only ensures visible opacity without compromising the mid-infrared transparency, but it also achieves cotton-like softness [ 4 ]. Conversely, to warm the human body, we showed for the first time that photonic crystal structuration of a synthetic polymer was able to increase the temperature of the human body [ 5 ]. For an appropriate set of geometric parameters, we found that the superior heating effect resulted in a 1 °C drop in the ambient temperature setting point.…”
Section: Introductionmentioning
confidence: 99%